KEPASTIAN HUKUM PENINGKATAN STATUS HAK ATAS TANAH YANG DIBEBANKAN HAK TANGGUNGAN DARI HAK GUNA BANGUNAN MENJADI HAK MILIK (Studi Pada Kantor Pertanahan Kota Solok) - Haraif Yudha Putra (UNES Journal of Swara Justisia, 2021)
Land is a very important need because all human activities take place on the ground. Provisions on land rights are regulated in Law no. 5 of 1960 concerning Basic Agrarian Regulations. Among the land rights there are Building Use Rights and Property Rights. And for this reason, it is necessary to register and upgrade from Hak Guna Bangunan to Hak Milik. Building use rights have a limited period of time and need to be upgraded to property rights in order to have legal certainty for the rights holders. The increase in HGB to become property rights must be registered at the Land Office where the object is located. The formulation of the problem in this study is, First, how is the implementation of increasing the status of land from building use rights to property rights at the Solok City Land Office? Second, what are the obstacles that occur in the implementation of increasing land status from building use rights to property rights at the Solok City Land Office? The specification of this research is descriptive analysis. The approach used in this study is a normative juridical approach Based on the results of the study, it was shown that (1) the implementation of the improvement of land status from building use rights to ownership rights at the Solok City Land Office was carried out based on sample certificates, namely increasing building use rights to property rights on house building land, in addition, in the process of increasing land rights from the use of the building becomes property rights by fulfilling the conditions specified in the laws and regulations and other regulations. (2) Obstacles that occur in the implementation of improving the status of land from building use rights to property rights at the Solok City Land Office due to the increase in rights caused by the lack of public knowledge regarding the increase in rights, such as in terms of costs, conditions, uses or benefits. of the increase in rights. In addition, an increase in the right to use a building that is encumbered with a mortgage can be carried out, but with the approval of the creditor and accompanied by the submission of a certificate of mortgage held by the creditor to the debtor.